2021
DOI: 10.2147/opth.s323058
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Outcomes After COVID-19-Related Treatment Interruption Among Patients with Neovascular Age-Related Macular Degeneration Receiving Intravitreal Bevacizumab

Abstract: Purpose: To assess outcomes and recovery strategy of patients undergoing intravitreal injections for exudative age-related macular degeneration who experienced COVID-19 related interruption in treatment during complete lockdown. Methods: This was a retrospective, observational case study. We used a mixed effect model with random intercepts to evaluate best corrected visual acuity (BCVA) accounting for measured central macular thickness (CMT) and individual variability of each eye. Furthermore, we analysed meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…COVID-19 pandemic has had severe consequences regarding medical care. Among AMD patients, anatomic and functional outcomes after COVID-19 lockdown have been widely analyzed [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. One year after pandemic outbreak and national lockdown, we are now able to assess long-term consequences of anti-VEGF treatment delay studying the anatomic and functional situation of these same patients after one year of regular follow-up and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 pandemic has had severe consequences regarding medical care. Among AMD patients, anatomic and functional outcomes after COVID-19 lockdown have been widely analyzed [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. One year after pandemic outbreak and national lockdown, we are now able to assess long-term consequences of anti-VEGF treatment delay studying the anatomic and functional situation of these same patients after one year of regular follow-up and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the effects of a month-long visit pause (4 months minimum follow-up time post-lockdown) on nAMD patients in a treat and extend setting, Allegrini et al found that in a cohort with a pre-lockdown visit interval of a mean 103 days, the observed VA loss of a mean 0.1 logMAR could not be clearly attributed to the 30-day visit interval increase [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study of a large Korean cohort (N = 135,435) showed that only the exudative (wet) form of AMD was significantly associated with severe COVID-19 illness and COVID-19 infection [6]. In addition, Allegrini et al found a significant loss in visual function among the exudative AMD patients who experienced COVID-19 infection compared to AMD patients before the pandemic [45]. Unfortunately, we were unable to evaluate genetic correlations between COVID-19 outcomes and exudative and non-exudative AMD separately because our analyses were conducted using AMD GWAS summary-level data.…”
Section: Discussionmentioning
confidence: 99%